Chiral selection of single helix formed by diblock copolymers confined in nanopores. Issue 35 (18th August 2016) - Deng, Hanlin; Qiang, Yicheng; Zhang, Tingting; Li, Weihua; Yang, Tao
Abstract : We study the stimuli-response of chiral selection of block copolymer self-assembly confined in nanopores to external conditions by introducing a chiral pattern to the nanopore inner surface, aiming to obtain a defect-free helix with controllable homochirality. Abstract : Chiral selection has attracted tremendous attention from the scientific communities, especially from biologists, due to the mysterious origin of homochirality in life. The self-assembly of achiral block copolymers confined in nanopores offers a simple but useful model of forming helical structures, where the helical structures possess random chirality selection, i.e. equal probability of left-handedness and right-handedness. Based on this model, we study the stimulus-response of chiral selection to external conditions by introducing a designed chiral pattern onto the inner surface of a nanopore, aiming to obtain a defect-free helix with controllable homochirality. A cell dynamics simulation based on the time-dependent Ginzburg–Landau theory is carried out to demonstrate the tuning effect of the patterned surface on the chiral selection. Our results illustrate that the chirality of the helix can be successfully controlled to be consistent with that of the tailored surface patterns. This work provides a successful example for the stimulus response of the chiral selection of self-assembled morphologies from achiral macromolecules to external conditions, and hence sheds light on the understanding of the mechanism of the stimulus response.